Spinal Cord Injury in Myelomeningocele: Prospects for Therapy - Janik, Karolina; Manire, Meredith A.; Smith, George M.; Krynska, Barbara (Frontiers in Cellular Neuroscience, 2020)
Myelomeningocele (MMC) is the most common congenital defect of the central nervous system and results in devastating and lifelong disability. In MMC, the initial failure of neural tube closure early in gestation is followed by a progressive prenatal injury to the exposed spinal cord, which contributes to deterioration of neurological function in fetuses. Prenatal strategies to control the spinal cord injury offer an appealing therapeutic approach to improve neurological function, although the definitive pathophysiological mechanisms of injury remain to be fully elucidated. Better understanding of these mechanisms at the cellular and molecular level is of paramount importance for the development of targeted prenatal MMC therapies to minimize or eliminate the effects of the injury and improve neurological function. In this review, we discuss the pathological development of MMC with a focus on in utero injury to the exposed spinal cord. We emphasize the need for better understanding of the causative factors in MMC spinal cord injury, pathophysiological alterations associated with the injury, and cellular and molecular mechanisms by which these alterations are induced.